2006
DOI: 10.1111/j.1532-849x.2006.00125.x
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Approach to Chairside Provisional Replacement of an Extracted Anterior Tooth: Use of Fiber‐Reinforced Ribbon‐Composites and a Natural Tooth

Abstract: Immediate chairside replacement of an extracted anterior tooth may contribute to a patient's comfort, treatment acceptance, and expectations of treatment; however, fabrication of a custom restoration in the anterior region of the mouth may result in an esthetic compromise for patients during the fabrication period. Chairside tooth replacement is an excellent application of fiber-reinforced composite resin technology. This article presents an innovative, affordable chairside procedure in which Ribbond Multi-Pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…Some have suggested the use of natural teeth as part of a cast metal resin-bonded frameworks for multiple tooth replacement 9. Recently though, a fibre reinforced composite, such as ribbond, has been used to provide interim fixed prosthesis for single tooth replacement 10. But these alternatives effectively splint the pontic to neighbouring sound teeth and hence raise the possibility of inhibiting the maxillary growth, particularly in the intercanine area 11.…”
Section: Discussionmentioning
confidence: 99%
“…Some have suggested the use of natural teeth as part of a cast metal resin-bonded frameworks for multiple tooth replacement 9. Recently though, a fibre reinforced composite, such as ribbond, has been used to provide interim fixed prosthesis for single tooth replacement 10. But these alternatives effectively splint the pontic to neighbouring sound teeth and hence raise the possibility of inhibiting the maxillary growth, particularly in the intercanine area 11.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical studies have shown that there is a relatively high failure rate ranging between 10.3 to 47%, depending on the technique used and follow-up observation period (22,(27)(28)(29)35). Recently, FRC materials have been introduced for the fabrication of fixed dental prostheses, root posts and periodontal splints and much research is currently being conducted for these clinical applications (36)(37)(38)(39)(40)(41)(42)(43). Conversely, very few studies have focused on the use of FRCs as orthodontic retainers (31,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…FPDs is used as transitional restoration during bone grafting and soft tissue grafts before implant placement 11 or when implant are placed 2-stage surgical protocol in the anterior segments. 12 Fiber reinforced composite restorations are achieved in a single visit, but it is a challenge to provide characterization and to obtain a smooth surface at the pontic area. 13 Therefore, an acrylic resin artificial teeth was used, but it is not recommended for use as a pontic except a provisional partial denture because of pure adhesion of composite resin to acrylic resin.…”
Section: Discussionmentioning
confidence: 99%